ANALYSIS OF THE FINANCIAL PERFORMANCE OF ORIGINAL LOCAL GOVERNMENT REVENUE OF KLATEN - Rachmansih, Bernadetha Kurnia Dewi; Asrihapsari, Andi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
This study aims to discover the financial performance of the Original Local Government Revenue (Indonesian: Pendapatan Asli Daerah, abbreviated PAD) of the Klaten Regency Local Government from 2018 to 2022. This study is quantitative and descriptive. Data analysis was performed using the independence ratio, effectiveness ratio, and contribution ratio. The results show the financial performance of the PAD of the Klaten Regency is very low. It is seen from the regional financial independence ratio from 2018 to 2022 that has a percentage of 17.57% with the pattern of instructive relationships. The PAD effectiveness ratio from 2018 to 2022 shows very effective criteria because the revenue exceeds 100% with a percentage of 115.11%. The PAD contribution ratio from 2018 to 2022 shows moderate criteria because it has a percentage of 25.00%. In addition, there are still several obstacles to increasing PAD experienced by the Klaten Regency Local Government. Based on the results of this study, the researchers give some recommendations, namely optimizing sources of PAD that have not been developed well, digitizing the payment system, promoting Local Government Owned Enterprises directly to the public through social media, and putting efforts to minimize obstacles to increasing PAD.